1,1,3-Trisubstituted cyclobutanes containing thiazole and thiourea fragments - Koparir, M; Cansiz, A; Ahmedzade, M (Khimiya Geterotsiklicheskikh Soedineniya, 2006)
The synthesis of 1-aryl-3-(2-chloro-1-hydroxyethyl)-1-methylcyclobutanes, 1-aryl-3-(2-chloro l-oxoethyl)-1-methylcyclobutanes, 2-amino-4-(3-aryl-3-methylcyclobutyl)thiazoles, and N-[4-(3-aryl-3-methylcyclobutyl)thiazole-2-yl]-N'-arylthioureas, is reported.
Keywords: Derivatives; Agents